Faktor-Faktor yang Mempengaruhi Terjadinya Depresi pada Remaja - Karokaro, Tati; Afrizal, Afrizal; Yanis, Amel; Hardisman, Hardisman (Journal of Telenursing (JOTING), 2024)
This study aims to build a family empowerment model in an effort to prevent depression in adolescents for their families, adolescents, and community mental health nurses in Deli Serdang Regency, North Sumatra. This research method uses a sequential explanatory design. The results of the study showed that there was no significant relationship between individual characteristics and the incidence of adolescent depression. There was a significant relationship between family emotional support and instrumental support with depression in adolescents. The results of this study conclude that families are expected to be able to foster good communication with children, especially adolescents. Keywords: Depression, Family Empowerment Model, Adolescents